LASER RADIATION MADE HYDROPHOBIC SURFACE ON STAINLESS STEEL FOR FOOD INDUSTRY, A REVIEW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2026)
Main requirement in food processing industry is providing a food safety through all the production cycle. One of many procedures that guarantee food safety is cleanliness of surfaces that are in contact with food or its raw materials. Surface cleanliness could be achieved in different ways, either by regular washing with clean water and detergents or by creating surfaces, that repel water or other residues. It is important, because remaining water with residues create conditions for growth of unwanted microflora. As classic, or active, cleaning method of washing with clean water and detergents require a lot of resources and energy. But nowadays more and more self cleaning, passive, methods are used, such as hydrophobic surfaces. These surfaces are made with in different ways, where most common are water reppeling coatings, for example – wax. But there are other methods, such as laser radiation treatment, that can create hydrophobic surface on required material, such as stainless steel, which is most common used material in food processing. There are studies that show effectivnes of laser radiation created hydrophobic surface for water repelling, but unfortunately, there are no researches found, that could provide information of such surface interaction with milk. As milk by itself is water emulsion with different nutrients, its most favourable environment for microbiological growth. By examining and analyzing different scientific articles, that are linked to topic of hydrophobic surface usage in food industry, it was concluded, that laser radiation made hydrophobic surfaces on stainless steel could have large potential. Especially in dairy industry, where such surface treatment could decrease risks of microflora growth and save resources and energy that are required for active washing process.